Preoperative identification of cardiac surgery patients at risk of receiving a platelet transfusion: The Australian Cardiac Surgery Platelet Transfusion (ACSePT) risk prediction tool - Flint, A.W.J.; Bailey, M.; Reid, Christopher; Smith, J.A.; Tran, L.; Wood, E.M.; McQuilten, Z.K.; Reade, M.C. (WILEY, 2020)
© 2020 AABB